2008
DOI: 10.1002/jcb.21768
|View full text |Cite|
|
Sign up to set email alerts
|

Bone morphogenetic protein‐7 regulates differentially the mRNA expression of bone morphogenetic proteins and their receptors in rat achilles and patellar tendon cell cultures

Abstract: Previous animal studies have suggested that certain bone morphogenetic proteins (BMPs) may be useful therapeutically in treating tendon healing. To better understand the relationship among the different BMPs in the healing process, we initiated the present study to examine the effects of a member of the BMP family, BMP-7 (also called Osteogenic Protein-1) on the temporal and spatial expression patterns of other BMPs and the BMP receptors in cell cultures of adult rat Achilles and Patellar tendons. Cultures fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
3
21
1
Order By: Relevance
“…59 Furthermore, proliferation and viability of tendon cells (originating from the bovine flexor tendon) and synthesis of DNA, collagen, and proteoglycans were increased dose-dependently after BMP-7 treatment. 61 In our study, the maximum effect was observed for a BMP-7 dosage of 1000 ng/mL This finding is in contrast to Yeh et al, 63 who observed declining effects beyond 50 to 100 ng/mL, and Tsai et al 59 (>400 ng/mL). However, several variables may account for a different response between these studies, such as different cell origin (animal patellar/medial collateral ligament cells vs human RC tenocyte-like cells), culture conditions or growth factor origin.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…59 Furthermore, proliferation and viability of tendon cells (originating from the bovine flexor tendon) and synthesis of DNA, collagen, and proteoglycans were increased dose-dependently after BMP-7 treatment. 61 In our study, the maximum effect was observed for a BMP-7 dosage of 1000 ng/mL This finding is in contrast to Yeh et al, 63 who observed declining effects beyond 50 to 100 ng/mL, and Tsai et al 59 (>400 ng/mL). However, several variables may account for a different response between these studies, such as different cell origin (animal patellar/medial collateral ligament cells vs human RC tenocyte-like cells), culture conditions or growth factor origin.…”
Section: Discussioncontrasting
confidence: 84%
“…Cell proliferation and COL-I expression of tendon cell cultures (originating from rodent Patellar and Achilles tendons) were affected dose-dependently. 63 Proliferation and expression of several markers of rodent collateral ligament cells were enhanced, whereas messenger ribonucleic acid levels of COL-I increased only slightly. 59 Furthermore, proliferation and viability of tendon cells (originating from the bovine flexor tendon) and synthesis of DNA, collagen, and proteoglycans were increased dose-dependently after BMP-7 treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In vitro studies showed promising results for the tissue engineering and repair of bone [143], cartilage [148], skin [19], nerve [66], myocardium [5] and tendon [28].…”
Section: Adipose-derived Stem Cellsmentioning
confidence: 99%
“…Animal studies have shown the ability of BMP-7 to induce cartilage and bone formation as well as promote tendon healing and repair in rats [79]. On the contrary, in a review conducted by Aspenberg [3], BMP-7 was said to reduce the strength of tendon and predominantly support bone growth at the site of the injured tendon.…”
Section: Bone Morphogenetic Protein-2mentioning
confidence: 99%